2013
DOI: 10.1021/la401156d
|View full text |Cite
|
Sign up to set email alerts
|

Dye Sensitization of Four Low Index TiO2 Single Crystal Photoelectrodes with a Series of Dicarboxylated Cyanine Dyes

Abstract: Four dicarboxylated cyanine dyes were used to sensitize single-crystal anatase (001), anatase (101), rutile (001), and rutile (100) surfaces. Incident photon to current efficiencies (IPCE) spectra and isotherms were gathered for the different combination of dyes and surfaces. The maximum coverage of the surface-bound dyes on the TiO2 crystal surfaces was determined by photochronocoulometric measurements. The IPCE spectra of the surface-bound dyes revealed that both the dye monomers and H-aggregates were both p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 33 publications
3
35
0
Order By: Relevance
“…b Spectra of dye A in the immobilised state involving experimental and theoretical spectra of (i) non-interacting dye molecule with both linkers (ii) interacting and non-interacting dye molecules with APTES linker (iii) interacting and non-interacting dye molecules with PEI linker ◂ Considering that the theoretical spectra indicates that only covalent bond formation does not cause such magnitude of red shift in absorption maxima, a possible reason is formation of aggregates [28] which was indicated in the case of dye A. Formation of such aggregates upon immobilization of carboxylate dyes on different surfaces has been reported by Mulhern et al [28] and Choi et al [53]. So formation of aggregates on the surface in our case is not an exception.…”
Section: Bi-carboxylic Bi-functional Dyesmentioning
confidence: 86%
“…b Spectra of dye A in the immobilised state involving experimental and theoretical spectra of (i) non-interacting dye molecule with both linkers (ii) interacting and non-interacting dye molecules with APTES linker (iii) interacting and non-interacting dye molecules with PEI linker ◂ Considering that the theoretical spectra indicates that only covalent bond formation does not cause such magnitude of red shift in absorption maxima, a possible reason is formation of aggregates [28] which was indicated in the case of dye A. Formation of such aggregates upon immobilization of carboxylate dyes on different surfaces has been reported by Mulhern et al [28] and Choi et al [53]. So formation of aggregates on the surface in our case is not an exception.…”
Section: Bi-carboxylic Bi-functional Dyesmentioning
confidence: 86%
“…1. R8 has a red shifted absorption maximum and is known to aggregate much more readily than G15, 30 allowing further investigation of aggregation effects on photoinjection yields.…”
Section: Introductionmentioning
confidence: 99%
“…32 The structural difference is an additional two carbons in the bridging carbon chain between the two cyanine groups extending the conjugation length from three to five carbons, as shown in Figure 1. R8 has a red-shifted absorption maximum and is known to aggregate much more readily than G15, 30 allowing for further investigation of aggregation effects on photoinjection yields.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Multiple BZA groups were introduced into porphyrin dyes in order to increase their binding capability. [10][11][12][13][14][15] However, a compromise in solar cell efficiency was observed. Imahori et al 16 found that energy conversion efficiency decreased when a second BZA group was introduced into the porphyrin.…”
Section: Introductionmentioning
confidence: 99%